Answer:
x= 15
Step-by-step explanation:
We can use cross products to solve this problem
7 2x+5
-- = --------
3 x
7x = 3(2x+5)
Distribute
7x = 6x +15
Subtract 6x from each side
7x-6x = 6x-6x+15
x = 15
Answer:
5/3
Step-by-step explanation:
4 × x = (6×3+2)/3
---> 4x = 20/3
----> x = 20/12
----> x=5/3
Hope it helps
Answer:
14
Step-by-step explanation:
9 10 11 12 13 14
Answer:
<em><u>T</u></em><em><u>H</u></em><em><u>E</u></em><em><u> </u></em><em><u>C</u></em><em><u>O</u></em><em><u>R</u></em><em><u>R</u></em><em><u>E</u></em><em><u>C</u></em><em><u>T</u></em><em><u> </u></em><em><u>A</u></em><em><u>N</u></em><em><u>S</u></em><em><u>E</u></em><em><u>R</u></em><em><u> </u></em><em><u>O</u></em><em><u>F</u></em><em><u> </u></em><em><u>T</u></em><em><u>H</u></em><em><u>I</u></em><em><u>S</u></em><em><u> </u></em><em><u>Q</u></em><em><u>U</u></em><em><u>E</u></em><em><u>S</u></em><em><u>T</u></em><em><u>I</u></em><em><u>O</u></em><em><u>N</u></em><em><u> </u></em><em><u>I</u></em><em><u>S</u></em><em><u> </u></em><em><u>5</u></em><em><u>.</u></em>
Step-by-step explanation:
Here,
a23=6
a12=5
a32=6
Now,
a23+a12-a32
=6+5-6
=5